2009
DOI: 10.1111/j.1528-1167.2008.01814.x
|View full text |Cite
|
Sign up to set email alerts
|

Are cortical tubers epileptogenic? Evidence from electrocorticography

Abstract: SUMMARYThe purpose of this study was to characterize the epileptogenicity of tubers and surrounding cortex in patients with tuberous sclerosis complex (TSC). Three pediatric patients with TSC and intractable epilepsy underwent surgical resection of tubers associated with epileptogenic foci. In all patients, presurgical imaging revealed a prominent tuber that correlated on electroencephalography (EEG) with frequent interictal epileptiform discharges and electrographic seizures. Intracranial electrocorticography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
110
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(120 citation statements)
references
References 26 publications
6
110
2
1
Order By: Relevance
“…These studies have identified important mechanisms leading to specific neuroanatomical pathologies that interrupt normal stages of cortical development. However, seizures can also arise in human brain regions not classified as disorganized Major et al, 2009), and clear evidence for a population of "epileptic" dysplastic neurons has failed to emerge (Cepeda et al, 2003;George and Jacobs, 2011). Using an animal model of human lissencephaly, we show that functional integration of granule cells within the malformed DG is disrupted by LIS1 haploinsufficiency.…”
Section: Discussionmentioning
confidence: 96%
“…These studies have identified important mechanisms leading to specific neuroanatomical pathologies that interrupt normal stages of cortical development. However, seizures can also arise in human brain regions not classified as disorganized Major et al, 2009), and clear evidence for a population of "epileptic" dysplastic neurons has failed to emerge (Cepeda et al, 2003;George and Jacobs, 2011). Using an animal model of human lissencephaly, we show that functional integration of granule cells within the malformed DG is disrupted by LIS1 haploinsufficiency.…”
Section: Discussionmentioning
confidence: 96%
“…Cortical tubers are considered to represent the neuropathologic substrate of epilepsy in TSC patients. Despite recent advances in imaging and electrophysiologic techniques, the functional role of tubers as the epileptogenic zone remains a matter of some debate [216][217][218][219]. Increasing evidence supports the importance of the perituberal cortex in TSC (for reviews see [165,218] and [219]).…”
Section: Epileptogenesismentioning
confidence: 99%
“…Despite recent advances in imaging and electrophysiologic techniques, the functional role of tubers as the epileptogenic zone remains a matter of some debate [216][217][218][219]. Increasing evidence supports the importance of the perituberal cortex in TSC (for reviews see [165,218] and [219]). Accordingly, although epilepsy surgery targeting tubers may result in seizure freedom, [216,220] some patients continue to have seizures after tuber resection and, in fact, cases of TSC patients becoming seizure-free after resection of nontuberal cortex have been reported [221] (for a review see [165]).…”
Section: Epileptogenesismentioning
confidence: 99%
“…Эпилеп-тогенная ткань в основе этого типа туберов отсутству-ет, что было документально подтверждено с помощью инвазивной фиксации ЭЭГ [49], и эти туберы не яв-ляются эпилептогенными, когда находятся строго ин-тракортикально, даже если их размер велик. Эпилеп-тогенными считаются туберы, которые окружены зоной ФКД -эти изменения видны в режиме Т2 и на изображениях, полученных при инверсии-вос-становлении с подавлением сигнала от свободной во-ды (FLAIR), они расцениваются экспертами как ФКД (изменения белого вещества с признаками ФКД) [14,28].…”
Section: детской неврологииunclassified